2016
DOI: 10.1002/etc.3554
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphate ester flame retardant concentrations and distributions in serum from inhabitants of Shandong, China, and changes between 2011 and 2015

Abstract: The production and use of brominated flame retardants have been increasingly restricted. Organophosphate esters (OPEs) have been widely used as substitutes for brominated flame retardants. However, little is yet known about human exposure to OPEs. The potential health risks posed by OPEs were assessed by determining the concentrations of 6 OPEs in pooled serum samples from residents of Shandong, China. The mean ∑ OPE concentrations in 2011 and 2015 were 680 ng/g lipid and 709 ng/g lipid, respectively. The most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 38 publications
(62 reference statements)
1
21
0
Order By: Relevance
“…9 Although long-term human exposure trends have not been assessed previously, to the best of our knowledge, short-term trends were recently evaluated in pooled samples from Chinese adults. 32 Ma et al reported no change in TPHP concentrations between samples collected in 2011 and 2015 in China, suggesting that exposure levels were relatively constant during this period. 32 Our results suggest that TPHP exposure may have started to decrease post-2011, suggesting that TPHP use as a flame retardant or in other applications could be decreasing.…”
Section: Resultsmentioning
confidence: 90%
“…9 Although long-term human exposure trends have not been assessed previously, to the best of our knowledge, short-term trends were recently evaluated in pooled samples from Chinese adults. 32 Ma et al reported no change in TPHP concentrations between samples collected in 2011 and 2015 in China, suggesting that exposure levels were relatively constant during this period. 32 Our results suggest that TPHP exposure may have started to decrease post-2011, suggesting that TPHP use as a flame retardant or in other applications could be decreasing.…”
Section: Resultsmentioning
confidence: 90%
“…The median concentration of total PEFRs was around 10-100 ng/g of lipids in breast milk from Sweden and several Asian countries, indicating that substantial exposure occurs at a young age via breastfeeding (Sunddkvist et al, 2010;Kim et al, 2014). The parent compounds (Liu et al, 2016;Zhao et al, 2016;Li et al, 2017;Ma et al, 2017;Qiao et al 2017) and their metabolites (Bui et al, 2017) were found in human serum and blood in a few studies. The metabolism of parent PEFRs tends to occur rapidly and the measurement of metabolites concentrations in urine is generally preferred to the invasive measurement of the nonmetabolized chemicals in serum for exposure assessment.…”
Section: Occurrence Of Pefrs In Other Human Samplesmentioning
confidence: 99%
“…The instrumental analysis procedure has been described previously (Schindler et al 2009a(Schindler et al , 2009bMa et al 2016). The gas chromatograph was fitted with a TG-5HT column (15-m length, 0.25-mm inner diameter, and 0.10-mm film thickness; Thermo Fisher Scientific).…”
Section: Instrumental Analysismentioning
confidence: 99%
“…All the DAP analytes eluted in < 19.5 min. The instrumental analysis procedure has been described previously (Schindler et al 2009a(Schindler et al , 2009bMa et al 2016). Van den Eede et al (2013b) has done the research to compare DAP analysis employed by liquid chromatographyÀelectrospray ionization(À) tandem mass spectrometry and gas chromatography-tandem mass spectrometry.…”
Section: Instrumental Analysismentioning
confidence: 99%
See 1 more Smart Citation